The white West fascism, unreason, and the paradox of modernity - Attia, Kader 1970- (Sternberg Press, 2023)
"Tracing the relation between fascism and settler colonialism. Ever since neofascist movements began to surge across the globe, liberal commentators have tried to put a name to what they are defending from these illiberal ideologies. The consensus is reason or rationality--after the Second World War, mainstream scholarship has supported the view that adherence to fascism is a thing of unreason. This distinction between reason and unreason, a tenet of Enlightenment thought, sustains the universal appeal of liberal democracy but leaves unexamined the paradoxes that haunt modernity, particularly its colonial foundation, thus obscuring the continuities between fascism and imperial policies. The White West contends that, without confronting the structuring force of race in the production and reproduction of global wealth disparities, fighting for reason only leads to flawed utopias in which a critique or disruption of capitalism is easily inflected in the direction of neofascism. This collection of writing by leading historians, theorists, and scholars is an attempt to engage the overlaps between philosophical predicates and colonial legacies, as well as the undertheorized continuities between fascism and settler colonialism."--
Keywords: Kolonialismus; Faschismus